(3GdTGaj aj TQM eSfO GdTGaYis - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s; (3CHh YHO Gddg eMeO Hf GOQjS GdTGaYjs
(3ChdgG (B:s
(3jHOC HcJGH GdQLYI hajg aUdGf GdaUd GdChd ai CMcGe GdQLYI s
(3BNQgG (B:s
(3jfJgi HGdaUd GdKGdK ai GdcPH Yf GdfHi Udi Gddg Ydjg hSde s
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs